Three decades of Professional Accountancy in Nigeria - Incorporating Accountants' Guide (V.I. Lagos NobleHouse Investment, 1995)
This publication is an attempt to capture the development of the Profession of Accountancy in Nigeria since inception in 1965
jbi, 21/03/2018
loan
Keywords: Odogun, Donald A. (ed)